Pengembangan media prezi untuk pemahaman nilai-nilai Pancasila Sila ke-2 pada pembelajaran tematik muatan PPKn kelas III SD Negeri Baran Bantul Yogyakarta - Handayani, Diva Ayu; Pratomo, Wachid; Nadziroh (CV. Kurnia Grup, 2023)
This study aims to 1) determine the development of Prezi learning media in thematic learning PPKn content in order to increase students' understanding of the values of the second Pancasila precept, 2) determine the feasibility test of Prezi learning media in thematic learning PPKn content in order to increase students' understanding of the values of the second Pancasila precept with the subject matter of practicing the second Pancasila precept (respecting the diversity of characteristics). This type of research uses the Research and Development method which refers to the 4D development procedure consisting of 4 stages, namely define, design, develop, and disseminate. Data collection techniques used at the define stage are observation and interviews and at the develop stage are validation sheets. The data analysis technique used is descriptive statistical analysis. The results of this study indicate that the Development of Prezi Media for Understanding the Values of the 2nd Pancasila Precepts in Class III PPKn Content Thematic Learning at SD Negeri Baran Yogyakarta, the subject matter of implementing the second precept of Pancasila (respecting the diversity of characteristics) obtains media feasibility results with a tendency for the product to be at good category. This can be seen from the validation results of media experts showing that the criteria are: Very Good (60%), Good (40%), Poor (0%), and Enough (0%). Then, the feasibility of the material contained in the developed Prezi learning media is: Very Good (61%), Good (39%), Less (0%), and Enough (0%). From the criteria that have been obtained, it can be concluded that Prezi media is appropriate for use in thematic learning of PPKn content with the subject of respecting the diversity of characteristics.